TINJAUAN LITERATUR: POTENSI TANAMAN OBAT SEBAGAI SUMBER ANTIOKSIDAN ALAMI - Fahrauk Faramayuda; Nurul Safirah Safrudin; Ari Sri Windyaswari (Jurnal Buana Farma, 2026)
Oxidative stress is a major driver of degenerative diseases, while synthetic antioxidants may pose long-term safety risks. The need for safer natural antioxidants has accelerated the exploration of medicinal plants, which are rich in bioactive compounds with antioxidant potential, particularly flavonoids and polyphenols. This systematic review aimed to classify antioxidant compounds from medicinal plants according to their phytochemical groups and to appraise their therapeutic potential based on recent pharmacological evidence. Articles published between 2015 and 2025 were retrieved from PubMed, Google Scholar, Garuda. Fifteen studies met the inclusion criteria for antioxidant activity testing. The review identified dominant antioxidant constituents, classified by chemical structure, including phenols, polyphenols, flavonoids, quercetin, and flavonoid–hydroquinone derivatives, reported across multiple plant species (Table 1). Plants consistently described as antioxidant sources were reundeu (Straurogyne elongata), moringa (Moringa oleifera), Indonesian bay leaf (Eugenia polyantha), water clover (Marsilea crenata), mango leaves (Mangifera indica), raru wood (Cotylelobium lanceolatum), and Jamaican cherry (Muntingia calabura), exhibiting moderate to strong antioxidant activity mainly in DPPH and FRAP assays. Overall, the findings indicate that antioxidant activity correlates with structural features such as the number and position of hydroxyl (–OH) groups, conjugated systems, and metal-chelating capacity. However, these compounds still face challenges related to poor stability and low bioavailability, suggesting that nanotechnology-based delivery systems may enhance formulation effectiveness. In conclusion, the plants reviewed contain promising antioxidant constituents, with quercetin and flavonoids emerging as the most active compounds, supporting their development as candidates for natural antioxidant-based phytopharmaceutical raw materials in Indonesia.